Quality of life in chronic kidney patients with renal replacement therapy through arteriovenous fistula - Ortega Paredes, Maria Gabriela; Montenegro Villavicencio, Medardo (Revista Universidad de Guayaquil, 2023)
Background: Terminal chronic kidney disease is considered one of the main causes of morbidity worldwide, being responsible for poor blood pressure and glycemic control, becoming a high health expense with an equally high mortality rate. However, given renal replacement treatments, morbidity rates have improved, but there are shortcomings regarding quality of life and hospital care indicators. Objective: This project established the correlation between the type of vascular access used in hemodialysis and quality of life using the EQ5d-5L score. Method: Through the use of a questionnaire and the use of the EQ5D - 5L quality of life scale, a cross-sectional study was carried out in hemodialysis patients at the IESS Quito Sur hospital. Results: With a total of 112 patients, 66.1% being men, with an average age of 61 years and the main comorbidity being DM II; 39.3% used CAT and the rest AVF/TEFP, with 36.6% of the cases assessed using the Barthel score being independent. We determined that the average quality of life through EQ5D-5L was 0.74, 56.8% of the CAT had good quality of life and 70.6% of the AVF/PTEF. In their indicators we have that mobility was compromised in 45.5% of TACs and AVFs, self-care compromised in 50% of TACs and 26.5% of AVF/PTEF, daily physical activity compromised in 65.9% of CATs and 58.8% of the FAV/PTEF, pain present in 63.6% of the TAC and 64.7% of the FAV/PTEF, anxiety present in 36.6 TAC and 57.4 FAV/PTEF. Conclusion: Demonstrating the superiority in quality of life in those vascular accesses associated with the use of fistulas or arteriovenous prostheses.
Keywords: hemodialysis; end-stage renal disease; catheter; fistula; quality of life